Certain Integral Formulae Involving Incomplete I-Functions - Bhatter, Sanjay; Jangid, Kamlesh; Meena, Sapna; Purohit, Sunil Dutt (Science & Technology Asia, 2021)
In this paper, we have determined some integral formulae of incomplete I-functions involving the exponential function, the Legendre polynomials and generalized Laguerre polynomials.